Antimicrobial resistance of Listeria monocytogenes isolated from seafood and humans in Iran. (November 2016) - Abdollahzadeh, Esmail; Ojagh, Seyed Mahdi; Hosseini, Hedayat; Ghaemi, Ezzat Allah; Irajian, Gholamreza; Naghizadeh Heidarlo, Masoud
Abstract: Fourteen Listeria monocytogenes isolates previously collected from seafood (n = 7) and human patients (n = 7) were studied for their antimicrobial susceptibility against eight common antimicrobials (ampicillin, penicillin, gentamicin, streptomycin, tetracycline, trimethoprim-sulfamethoxazole, chloramphenicol, and cefotaxime). A high resistance level to ampicillin, cefotaxime (100%), and pencillin (57% in seafood isolates and 71.4% in clinical isolates) was observed in this study. However, all of the isolates were susceptible to trimethoprim-sulfamethoxazole, chloramphenicol, and tetracycline. Simultaneous resistance was identified in 4 clinical isolates (57.1%). Genotypic characterization of fish isolates (isolated from three fish species) was performed by pulsed-field gel electrophoresis (PFGE). A high diversity among fish isolates was observed. PFGE analyses distinguished the 4 isolates into 4 reproducible pulsotypes. There was no correlation between the antibiograms with pulsotypes. In conclusion, the resistance of seafood isolates to the antibiotics commonly used to treat listeriosis could be a potential health hazard for consumers. Highlights: High resistance prevalence among the isolates to at least one antibiotic. 100% of Listeria monocytogenes isolates were resistant to ampicillin. PFGE analysis of the 4 fish isolates gave 4 different PFGE profiles.